Implications of ongoing neural development for the measurement of the error‐related negativity in childhood. Issue 3 (11th September 2014) - DuPuis, David; Ram, Nilam; Willner, Cynthia J.; Karalunas, Sarah; Segalowitz, Sidney J.; Gatzke‐Kopp, Lisa M.
Abstract Event‐related potentials (ERPs) have been proposed as biomarkers capable of reflecting individual differences in neural processing not necessarily detectable at the behavioral level. However, the role of ERPs in developmental research could be hampered by current methodological approaches to quantification. ERPs are extracted as an average waveform over many trials; however, actual amplitudes would be misrepresented by an average if there was high trial‐to‐trial variability in signal latency. Low signal temporal consistency is thought to be a characteristic of immature neural systems, although consistency is not routinely measured in ERP research. The present study examined the differential contributions of signal strength and temporal consistency across trials in the error‐related negativity (ERN) in 6‐year‐old children, as well as the developmental changes that occur in these measures. The 234 children were assessed annually in kindergarten, 1st, and 2nd grade. At all assessments signal strength and temporal consistency were highly correlated with the average ERN amplitude, and were not correlated with each other. Consistent with previous findings, ERN deflections in the averaged waveform increased with age. This was found to be a function of developmental increases in signal temporal consistency, whereas signal strength showed a significant decline across this time period. In addition, average ERN amplitudes showed low‐to‐moderate stability across the three assessments whereas signal strength was highly stable. In contrast, signal temporal consistency did not evidence rank‐order stability across these ages. Signal strength appears to reflect a stable individual trait whereas developmental changes in temporal consistency may be experientially influenced.